OPPORTUNITIES FOR THE USE OF FOREIGN EXPERIENCE IN EXPORT ACTIVITIES OF SMALL BUSINESS AND BUSINESS ENTITIES IN UZBEKISTAN - Nishonboyev Doniyor Erkinjon o‘g‘li (Scientific Trends, 2024)
Small business and private entrepreneurship are of particular importance in the economic development of our country, the sustainable development of the economy of the regions, the employment of the population, and today its role and importance are growing even more. Therefore, the rapid development of small business and private entrepreneurship is the main link in ensuring the sustainable growth of the economy of any country and a priority of the economic reforms being carried out.
Keywords: entrepreneurship, business entities, profit, enterprise, product, export, import.